Coinheritance of the c.-19 G > C and c.315 + 1 G > A Variants in the β-Globin Gene Leads to Thalassemia Disease: A Report from the North of Iran - Hossein Jalali; Mahan Mahdavi; Mohammad Eslamijouybari; Mohammad Reza Mahdavi (Case Reports in Genetics)
Up to now, more than 300 pathogenic variants have been identified in the β-globin gene, some of which are categorized as silent mutations that do not change the hematological indices. In the present study, our aim is to introduce the first report of a case with thalassemia intermedia with coinheritance of the c.315 + 1 G > A pathogenic variant and a silent variant (HBB: c.-19 G > C) that was missed during the screening program. Multiplex-Gap-PCR and Sanger sequencing methods were applied to identify α- and β-globin gene mutations in a 26-year-old male subject with diagnosis of thalassemia. The identified mutations were also checked on the parent’s sample. The CBC and capillary electrophoresis tests were performed on the parent’s blood samples. The case was compound heterozygote for the c.315 + 1 G > A and c.-19 G > C (rs1239893012) variants. The subject’s mother carried the c.-19 G > C variant in the β-globin gene while her CBC and electrophoresis test results showed a normal pattern. Silent mutations are susceptible to being missed during premarital screening of β-thalassemia carriers, and the c.-19 G > C variant is recommended to be classified as a pathogenic variant in the β-globin gene.